Fizicke i fizioloske karakteristike vrhuskih srpskih fudrai skih sportista - Ostojic, S. M. (Facta Universitatis: Series Physical Education and Sport, 2000)
The purpose of this study was to describe structural and functional characteristics of elite Serbian soccer players and to make comparisons with non-elite counterparts. One of the teams in the study (Squad A; nA = 16) competed in the professional First National League while the other team (Squad B; nB = 16) played in the amateur Third Division. Physiological measurements were made in 32 players, during the final week of the preparatory training period. Subjects from Squad A were older (23.8 +/- 3.4 vs. 21.5 +/- 3.2 years, P < 0.05) and more experienced (7.5 +/- 3.1 vs. 4.8 +/-2.8 years, P < 0.05) as compared to players in Squad B. Players from Squad B had significantly lower estimated VO2 max values compared with elite subjects in Squad A (42.9 +/- 6.6 vs. 53.5 +/- 8.6 ml/kg-1min-1, P < 0.05). In addition, the highest heart rate frequencies during the last minute of the 20-m shuttle run test were lower in elite players (183.1 +/- 6.1 vs. 189.9 +/- 8.1 beats?min-1, P < 0.05). Vertical jump height was significantly higher in Squad A (47.6 +/- 5.7 vs. 46.2 +/- 5.5 cm, P < 0.05) and estimated percentage of fast muscle fibers (fast twitches) were higher in Squad A as compared to Squad B (62.8 +/- 7.7 vs. 57.4 +/- 8.1%, P < 0.05). The results of the present study support previous investigations indicating a strong relationship between aerobic fitness, anaerobic power and performance results in elite soccer.